Integrating Sustainability through Ecological Architecture in Apartment - Harisdani, Devin Defriza; Siregar, Masri Elysha (Komunitas Menulis dan Meneliti (Kolibi), 2024)
The rapid population growth in Deli Serdang has led to increased demand for vertical housing like apartments. However, unsustainable apartment development can harm the environment. Therefore, it's crucial to integrate sustainability principles, such as ecological architecture and green technology, in apartment design and construction. Additionally, the presence of apartments necessitates commercial facilities like community malls to cater to residents' daily needs. Integrating community malls with apartments can foster a more inclusive and sustainable environment by offering essential services and products while considering environmental impacts. This integration not only addresses housing demands but also enhances residents' living conditions and preserves the local ecosystem's balance. Hence, a holistic approach emphasizing sustainability and ecological architecture is essential for developing and managing both commercial and residential buildings in Deli Serdang.